Distributed Computing and Artificial Intelligence, Special Sessions I, 21st International Conference - Mehmood, Rashid; Hernández, Guillermo; Praça, Isabel; Wikarek, Jaroslaw; Loukanova, Roussanka; Monteiro dos Reis, Arsénio; Skarmeta, Antonio; Lombardi, Eleonora (Lecture Notes in Networks and Systems, 2025)
XVII, 431 p. 113 illus., 87 illus. in color.